Genetic Algorithms and Particle Swarm Optimization Mechanisms for Through-Silicon Via (TSV) Noise Coupling. (24th May 2021) - Ait Belaid, Khaoula; Belahrach, H.; Ayad, H.
Abstract : In this paper, two intelligent methods which are GAs and PSO are used to model noise coupling in a Three-Dimensional Integrated Circuit (3D-IC) based on TSVs. These techniques are rarely used in this type of structure. They allow computing all the elements of the noise model, which helps to estimate the noise transfer function in the frequency and time domain in 3D complicated systems. Noise models include TSVs, active circuits, and substrate, which make them difficult to model and to estimate. Indeed, the proposed approaches based on GA and PSO are robust and powerful. To validate the method, comparisons among the results found by GA, PSO, measurements, and the 3D-TLM method, which presents an analytical technique, are made. According to the obtained simulation and experimental results, it is found that the proposed methods are valid, efficient, precise, and robust.